Cystitis in a sow due to Corynebacterium suis - Too, H. L.; Chooi, K. F.; Bahaman, Abdul Rani (Persatuan Doktor Veterinar Malaysia, 1985)
A clinical case of cystitis in a sow due to Corynebacterium suis is reported. Haematuria was observed twice - after mating and after parturition. Necropsy revealed a chronic 'haemorrhagia cystitis. Corynebacterium suis was isolated from the urinary bladder using anaerobic culture techniques